Penerapan Good Governance dan Internal Control terhadap Quality of Financial Statements - Muhammad Ridho Ariansyah; Henny Yulsiati; Evada Dewata (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study aims to analyze the influence of Good Governance and Internal Control on the Quality of Financial Statements of hospitals with BLU and BLUD status in South Sumatra Province, as well as to examine the differences in financial reporting quality between the two. This study aims to examine the contribution of each variable identified as the topic of discussion. This study specifically examines the contribution of internal controls and sound mechanisms. Employing a quantitative methodology, this research utilized purposive sampling to gather data from 53 respondents, including personnel from Finance, Budgeting, Internal Audit, and Financial Administration. The primary data were collected and analyzed through instrument testing, classical assumption testing, descriptive statistics, hypothesis testing, mean difference testing, and multiple linear regression. The results indicate that Good Governance has a significant positive effect on the Quality of Financial Statements, as shown by a t-value of 2.965, which is higher than the t-table value of 1.675. However, Internal Control does not contribute to the Quality of Financial Statements, as indicated by a t-value of 1.477, which is lower than the t-table value of 0.1675. Simultaneously, all independent variables have a significant effect on the Quality of Financial Statements, as evidenced by an F-value of 10.712, which is greater than the F-table value of 3.18, with a significance value of 0.001 (<0.05). Interestingly, there is no significant difference in the Quality of Financial Statements between Regional Public Service Agency (BLUD) hospitals and Public Service Agency (BLU) hospitals, as indicated by significance values of 0.629 and 0.620, both of which are greater than 0.05.